Implementation of Edwin Guthrie and Watson's Behavioristic Conditioning Learning Theory in the Learning of Grade V Elementary School Students - Sulisthia, Putu Sri; Suarni, Ni Ketut; Margunayasa, I Gede (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
This study aims to analyze the effectiveness of the conditioning theory put forward by Edwin Guthrie and John Watson in increasing the involvement and understanding of grade V elementary school students. The research subjects consisted of 31 students who were randomly selected from one of the elementary schools. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and learning outcome tests. Data analysis was carried out with a thematic approach based on the results of observations and interviews, as well as simple quantitative analysis to measure the improvement of students' academic scores. The results of the study showed that the application of the conditioning method had a positive impact on students' motivation in learning, where they were more active in the classroom after being given positive reinforcement in the form of praise and small rewards. In addition, light punishments such as point deductions also contribute to improving learning discipline. However, there were some students who did not experience significant changes, suggesting that this method needed to be combined with other approaches to achieve more optimal results. The implication of this study is the need to develop more varied learning methods by considering the characteristics of different students. Teachers are advised to flexibly adapt conditioning strategies and combine them with other approaches, such as cognitive-based or constructivist learning, to increase the effectiveness of learning. In addition, further research with a wider scope can be conducted to obtain a more comprehensive understanding of the impact of conditioning in the context of elementary school learning. Penelitian ini bertujuan untuk menganalisis efektivitas teori conditioning yang dikemukakan oleh Edwin Guthrie dan John Watson dalam meningkatkan keterlibatan dan pemahaman siswa kelas V SD. Subjek penelitian terdiri dari 31 siswa yang dipilih secara random sampling dari salah satu sekolah dasar. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan tes hasil belajar. Analisis data dilakukan dengan pendekatan tematik berdasarkan hasil observasi dan wawancara, serta analisis kuantitatif sederhana untuk mengukur peningkatan nilai akademik siswa. Hasil penelitian menunjukkan bahwa penerapan metode conditioning berdampak positif terhadap motivasi siswa dalam belajar, di mana mereka lebih aktif dalam kelas setelah diberikan penguatan positif berupa pujian dan reward kecil. Selain itu, hukuman ringan seperti pengurangan poin juga berkontribusi dalam meningkatkan disiplin belajar. Namun, terdapat beberapa siswa yang tidak mengalami perubahan signifikan, menunjukkan bahwa metode ini perlu dikombinasikan dengan pendekatan lain untuk mencapai hasil yang lebih optimal. Implikasi dari penelitian ini adalah perlunya pengembangan metode pembelajaran yang lebih bervariasi dengan mempertimbangkan karakteristik siswa yang berbeda. Guru disarankan untuk mengadaptasi strategi conditioning secara fleksibel dan mengombinasikannya dengan pendekatan lain, seperti pembelajaran berbasis kognitif atau konstruktivis, untuk meningkatkan efektivitas pembelajaran. Selain itu, penelitian lebih lanjut dengan cakupan yang lebih luas dapat dilakukan untuk mendapatkan pemahaman yang lebih komprehensif tentang dampak conditioning dalam konteks pembelajaran sekolah dasar.